R&D in Brazilian Industry recent indicators - Sbragia, Roberto
Roberto Sbragia and Isak Kruglianskas summarize spending data from Brazil's first industrial technology database project.
Information provided by 500 companies indicates that Brazil's industry is spending more on science and technology.
On the assumption that the intensity with which firms engage in building technological capability is a key to entrepreneurial success, Brazil is implementing a Technology Indicators Database of industrial companies. Longitudinal analysis and comparisons among businesses from different sectors, size and origin of capital are the focus of this project, which is being undertaken by the National Association for R&D of Industrial Firms (ANPEI). Data already stored in the base, with reference to 1994, involving 500 companies that account for almost 41 percent of Brazil's industrial GNP, indicate that these firms spent, on average, US 2.8 million dollars in R&D&E operating expenses and reported US 1.5 million dollars in direct or indirect cost reduction from these activities. Information in the database allows companies to compare themselves on R&D spending, personnel, patents, project completions, revenues from new products, and cost savings.
Keywords: R&D--Brazil.